Análise econômica do uso dos insumos na produção de leite, na região de Viçosa, Zona da Mata, Minas Gerais - Borzino Ferreira da Silva, Sérgio Luiz; Leitão e Silva, Josué; Dias Teixeira , Teotônio (Revista Ceres, 2025)
This study was conducted in the region of Viçosa in the «Zona da Mata» of Minas Gerais and had as its objective the investigation of inputs used in milk production with data collected in 1968/69.